2019
DOI: 10.14221/ajte.2018v44n2.1
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Preservice Science Teachers’ Environment-Friendly Behaviours

Abstract: The purpose of this study was to examine the relationships among the preservice science teachers' proenvironmental behaviours, environmental identity, and ecocentric and anthropocentric attitudes toward environment. A total of 576 (407 females and 169 males) preservice science teachers enrolling in five public universities' education faculties in Eastern and Southeastern Anatolian Region of Turkey were administered a questionnaire regarding the variables. Convenience sampling method was chosen to constitute th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 43 publications
0
9
0
2
Order By: Relevance
“…In every one of these activities the job of ladies is by all accounts especially significant (Xiao & Hong, 2010). Numerous logical examinations have been directed researching the relationship of sex to cooperation in ecological activities (Uçar & Canpolat, 2019;Zelezny, Chua, & Aldrich, 2000), just as other investigate considers concentrating on every day home vitality sparing practices e.g., (Carlsson-Kanyama & Lindén, 2007;Räty & Carlsson-Kanyama, 2010). Albeit a few examinations have discovered no sex contrasts in ecological practices (Blankenau, Snowden, & Langan, 2007), most investigations presume that ladies have a more significant level of ecological conduct than men (Lee, 2009;Torgler, Garcia, & Macintyre, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In every one of these activities the job of ladies is by all accounts especially significant (Xiao & Hong, 2010). Numerous logical examinations have been directed researching the relationship of sex to cooperation in ecological activities (Uçar & Canpolat, 2019;Zelezny, Chua, & Aldrich, 2000), just as other investigate considers concentrating on every day home vitality sparing practices e.g., (Carlsson-Kanyama & Lindén, 2007;Räty & Carlsson-Kanyama, 2010). Albeit a few examinations have discovered no sex contrasts in ecological practices (Blankenau, Snowden, & Langan, 2007), most investigations presume that ladies have a more significant level of ecological conduct than men (Lee, 2009;Torgler, Garcia, & Macintyre, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Among the goals of sustainable development is the need to step up efforts to protect and preserve cultural heritage. It recognizes cultural diversity and promotes the view that all cultures and cultures can contribute to the achievement of sustainable development (Uçar & Canpolat, 2019). The perspective of culture can help rede ine our goals and approaches by integrating cultural diversity issues into sustainable development (Tilbury & Mulà, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Within this context, women actively protecting tradition by continuing it and creating works of high cultural value, contribute signi icantly to the cultural dimension of sustainability, thereby necessitating the emergence of their important cultural sustainable work . According to data from scienti ic research investigating the relationship of gender to participation in environmental actions (Uçar & Canpolat, 2019;Zelezny, Chua, & Aldrich, 2000). It is found that women have higher level of environmentally friendly behavior compared to men (Torgler, Garcia-Valiñas, & Macintyre, 2008;Lee, 2009), although some studies have found that there are no gender differences in environmental behavior (Blankenau, Snowden, & Langan, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Para educar hacia los objetivos de desarrollo sostenible (SDGs), los enfoques centrados en las personas, orientados a la acción y transformadores, representan la forma más eficiente de capacitar a los estudiantes para un comportamiento proambiental en su diario accionar (Saldaña-Almazán, et al, 2020). Una alternativa directa de promover el comportamiento proambiental dentro del ámbito educativo es aquella que involucra el modelamiento de dicha conducta por parte de figuras de autoridad que sean respetadas y admiradas, tales como padres y profesores (Djuwita & Benyamin, 2022;Jia & Yu, 2021;Uçar & Canpolat, 2019).…”
Section: Introductionunclassified